Patterns of seedling recruitment in West-Mediterranean Quercus ilex forest influenced by canopy development - Espelta, Josep Maria; Riba, Miquel; Javier, Retana (Journal of Vegetation Science, 1995)
Abstract. Quercus ilex (holm oak) coppice forests belong to the most representative communities in the western part of the Iberian Peninsula. Due to the high sprouting potential of holm oak after coppicing, the dynamics of recruitment of new individuals in existing populations has been largely overlooked. In these forests, the density of seedlings increases in old stands, as a result of the remarkable increase in the recruitment of 1-yr and 2-yr old seedlings, probably due to better environmental conditions for germination. Older seedlings show a tendency towards increasing survival under some degree of canopy closure, since their density appears to be higher just before complete canopy closure takes place. Nevertheless, the reduced growth of seedlings in older stands due to low light levels causes age distributions of holm oak seedlings to change drastically, with saplings older than 15 yr becoming very unusual in these stands. Therefore, a bottleneck of recruitment appears at this sapling stage and prevents vigorous regeneration just before thinning. Present conditions of genet density and management tend to prevent population renewal. Dynamics of the seedling bank reinforce the role of gap formation through small or large scale perturbations in population turnover.
Keywords: Holm oak; Regeneration; Seeder; Seedling dynamics; Sprouter; thinning